GENERATION Z DRAMATURGY THROUGH TIKTOK SOCIAL MEDIA AS A MEDIUM OF SELF-REPRESENTATION - Amirullah, Sumaslichah Dwi Lestari; Siregar, Nadia Itona (Jurusan Ilmu Komunkasi FISIP Universitas Jenderal Soedirman, 2024)
Abstract. TikTok is one of the social networking applications and is popular in the world including Indonesia. The emergence of TikTok is the phenomenon that attracts the most attention from various groups, especially Generation Z. Users of this application are dominated by teenagers, namely students and college students, where users use it to express themselves, release boredom, find the information or knowledge, and/or just watch videos as entertainment. The popularity of TikTok has made the boundaries between privacy and public space blurred, allowing for differences in behavior among teenagers. This research aims to find out how Generation Z’s self-representation through TikTok social media. This research uses the concept of self-representation that refers to Erving Goffman’s Dramaturgy Theory. This research uses qualitative research methods with a phenomenological approach. Data collection techniques were carried out by conducting observations and interviews with 4 informants. The results of this study indicate that the four informants perform self-representation through the TikTok application by building the desired self-image and maintaining the authenticity displayed between social media and daily life, which is not much different.